2022
DOI: 10.21203/rs.3.rs-1465797/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Care Practice and Associated Factors Among Patients with Type 2 Diabetes Mellitus at a Referral Hospital in Northern Ethiopia – a Mixed Methods Study

Abstract: Introduction: Diabetes self-care is important to maintain optimal glycemic control and prevent debilitating and costly complications. Diabetes self-care may be improved through the identification of individual and group barriers to regimen adherence and subsequent development of specific plans to overcome these barriers. This study assessed the self-care practice and associated factors among type 2 diabetes patients attending their treatment at Dessie Referral Hospital, Dessie, North-Eastern Ethiopia. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…A study conducted in Northern Ethiopia revealed that the overall good self-care practice was 50.3%. This study also showed that 39.3% and 54.9% of the study participants had good exercise and diet adherence, respectively [14]. Another survey from Ethiopian General Hospital indicated that (63.1%) of study participants had good self-care practices.…”
Section: Introductionsupporting
confidence: 54%
“…A study conducted in Northern Ethiopia revealed that the overall good self-care practice was 50.3%. This study also showed that 39.3% and 54.9% of the study participants had good exercise and diet adherence, respectively [14]. Another survey from Ethiopian General Hospital indicated that (63.1%) of study participants had good self-care practices.…”
Section: Introductionsupporting
confidence: 54%